Versatile roles of V-ATPases accessory subunit Ac45 in osteoclast formation and function. - An Qin (Public Library of Science (PLoS), 2011)
Vacuolar-type H(+)-ATPases (V-ATPases) are macromolecular proton pumps that acidify intracellular cargos and deliver protons across the plasma membrane of a variety of specialized cells, including bone-resorbing osteoclasts. Extracellular acidification is crucial for osteoclastic bone resorption, a process that initiates the dissolution of mineralized bone matrix. While the importance of V-ATPases in osteoclastic resorptive function is well-defined, whether V-ATPases facilitate additional aspects of osteoclast function and/or formation remains largely obscure. Here we report that the V-ATPase accessory subunit Ac45 participates in both osteoclast formation and function. Using a siRNA-based approach, we show that targeted suppression of Ac45 impairs intracellular acidification and endocytosis, both are prerequisite for osteoclastic bone resorptive function in vitro. Interestingly, we find that knockdown of Ac45 also attenuates osteoclastogenesis owing to a reduced fusion capacity of osteoclastic precursor cells. Finally, in an effort to gain more detailed insights into the functional role of Ac45 in osteoclasts, we attempted to generate osteoclast-specific Ac45 conditional knockout mice using a Cathepsin K-Cre-LoxP system. Surprisingly, however, insertion of the neomycin cassette in the Ac45-Flox(Neo) mice resulted in marked disturbances in CNS development and ensuing embryonic lethality thus precluding functional assessment of Ac45 in osteoclasts and peripheral bone tissues. Based on these unexpected findings we propose that, in addition to its canonical function in V-ATPase-mediated acidification, Ac45 plays versatile roles during osteoclast formation and function.